The impact of crystalloid versus colloid on coagulation as measured by thromboelastometry in term parturients: an in vitro study. (12th December 2022) - Getrajdman, Chloe; Sison, Matthew; Lin, Hung-Mo; Katz, Daniel
Abstract: Objective: A pilot study to examine the impact of crystalloid versus albumin hemodilution in vitro on coagulation using thromboelastometry in pregnant patients. Methods: This prospective, observational pilot study included seventy-six pregnant patients at term (≥37 weeks) without history of bleeding or clotting disorder or on anticoagulation. Blood was collected and diluted with either Plasma-Lyte or albumin at the following levels: 0%, 20%, 25%, 30%, 35%, 40%, 45%, 55%, 60%, 65%, 70%, 75%, 80%. Thromboelastometry was performed to assess for coagulation changes. Results: There was a small, statistically significant difference in the FIBTEM A5 between the Plasma-Lyte and albumin samples. However, the predicted probability of coagulopathy, using FIBTEM A5 less than 12 mm, was not different between the groups at any dilution. There was no difference in EXTEM clotting time at low-moderate levels of hemodilution. At dilutions above 40%, the albumin group had a significantly greater prolongation in clotting time compared to the Plasma-Lyte group. Conclusion: When albumin is used at low-moderate levels of hemodilution in vitro in parturients there is no additional risk of coagulopathy compared to hemodilution with crystalloid. Given that colloids are frequently used to restore intravascular volume during massive hemorrhage, these results support that during early stages of hemorrhage, albumin may not contribute to additional coagulopathy beyond that of hemodilution, although further in vivo studies are needed.